¿Lengua de inmigración o lengua extranjera? Enseñanza del putonghua en una escuela pública de la Ciudad de Buenos Aires - Sartori, María Florencia (2023)
This paper analyzes, from a glotopolitical perspective, the establishment and functioning of a Spanish-Putonghua bilingual public school in the city of Buenos Aires. This institution and its implementation demonstrate a concern for the educational inclusion of Chinese migrants and their descendants, as well as for the preservation and learning of the immigration language. Throughout this article, we will show how Putonghua is constructed both as a language of instruction and as an “object language” in legal regulations, classes, and in the speeches of officials. We argue that the motivation underlying the creation of this school is the increasing importance that Putonghua has gained globally in recent years.